2004
DOI: 10.1577/a04-018.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hatchery Performance Attributes among Three Strains of Age‐0 Coaster Brook Trout

Abstract: The hatchery performance attributes of three strains (Lake Nipigon [Nipigon], Siskiwit Bay [Siskiwit], and Tobin Harbor [Tobin]) of fingerling coaster brook trout Salvelinus fontinalis were compared during a 12‐week laboratory experiment. Despite similar initial sizes, the final mean length and weight of Nipigon fish (94.1 mm and 9.9 g) were significantly greater than those of the Siskiwit (86.7 mm and 7.7 g) and Tobin (90.4 mm and 7.2 g) strains. There were no differences in mean specific growth rates in leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In comparison, studies of wild brook trout (Morinville and Rasmussen 2003;Thériault and Dodson 2003) and brown trout (Forseth et al 1999) showed that migrants have higher energy consumption than their resident counterparts, but show no difference in growth rate. Also in our study, NIP had larger initial masses and lengths than all other strains, which is similar to results of Volkman et al (2004), who also found that age 0 NIP exhibited more growth in length and mass than both SIS and TBH, without differences in W r , using similar laboratory conditions. This study also demonstrated that morphological differences can be detected between Lake Superior basin brook trout strains; however, morphological traits associated with smoltification and open water habitats were not consistently seen in the adfluvial and lacustrine strains.…”
Section: Discussionsupporting
confidence: 91%
“…In comparison, studies of wild brook trout (Morinville and Rasmussen 2003;Thériault and Dodson 2003) and brown trout (Forseth et al 1999) showed that migrants have higher energy consumption than their resident counterparts, but show no difference in growth rate. Also in our study, NIP had larger initial masses and lengths than all other strains, which is similar to results of Volkman et al (2004), who also found that age 0 NIP exhibited more growth in length and mass than both SIS and TBH, without differences in W r , using similar laboratory conditions. This study also demonstrated that morphological differences can be detected between Lake Superior basin brook trout strains; however, morphological traits associated with smoltification and open water habitats were not consistently seen in the adfluvial and lacustrine strains.…”
Section: Discussionsupporting
confidence: 91%
“…Option I (Inherent Energetic Hypothesis) hinges on inherent differences between individual brook trout where one group (the coasters) has a different growth potential than the other (residents). Support for this hypothesis comes from Volkman et al (2004) where growth differences were demonstrated between commonly reared coaster brook trout strains, although their results were confounded by population differences among life history variants. The Inherent Energetic Hypothesis posits that even as juveniles in the natal stream these metabolic differences would be present as suggested for anadromous brook trout (Morinville and Rasmussen, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using mtDNA (BurnhamCurtis 1996), and life history differences exhibited in the wild (Newman et al 1999;Quinlan et al 1999) and the hatchery (Volkman et al 2004), support this program goal. We found a moderately large F st between the strains (TH01W-SB01 W F st = 0.13, 95% CI = 0.08-0.19) and between each strain and the RC strain (TH01W-RC F st = 0.20, 0.09-0.33; SB01W-RC F st = 0.29, 0.12-0.50), confirming population differentiation.…”
Section: Maintaining Population Differentiationmentioning
confidence: 99%